Impacts of mussel invasions on the prey preference of two native predators. (21st December 2017) - Skein, Lisa; Robinson, Tamara B; Alexander, Mhairi E
Abstract : Alien prey alter food choices available to native predators; and, when these prey are not selected for consumption, their invasion may be facilitated. We show that even predators with a broad diet may actively avoid alien prey and selectively feed on native species, despite alien prey being more abundant and easier to consume. This lack of predation pressure combined with the removal of competing native prey offers 2 sources of facilitation of prey invasions. Abstract: Biotic invasions can result in the displacement of native species. This can alter the availability of native prey and the choices made by native predators. We investigated prey selection by 2 native South African predators, the west coast rock lobster Jasus lalandii and the starfish Marthasterias africana in response to the invasive mussels, Mytilus galloprovincialis and Semimytilus algosus, and native mussels, Aulacomya atra and Choromytilus meridionalis . As the diets of lobsters and starfish are broad and have been suggested to reflect prey availability, we hypothesized that they would consume the most abundant prey, regardless of its native or alien status. Laboratory studies presented predators with varying proportions of native and invasive mussels that represented pre- and post-invasion scenarios. Mussel parameters (shell strength, adductor muscle size, and energy content) that may be of importance in selection by predators were compared among species. Both predators exhibited preference towards the native mussel C. meridionalis, even when it was the least abundant prey. The selection of native species occurred despite mussel parameters suggesting that invasive species would be easier to consume. These findings highlight the potential for facilitation of prey invasions, especially when predators avoid alien prey and select for native comparators that may offer resistance to the invasion through inter-specific competition. It is presently unclear how often such a lack of predator-driven biotic resistance acts in combination with indirect facilitation, but interrogating the behaviors that drive such outcomes will advance our understanding of successful invasions.